The first discovery of a skull trepanated by drilling on Middle Bronze Age materials from the North Caucasus. - Pererva, Evgenij Vladimirovic; Berezina, Natal'a Akovlevna; Mataev, Vasilij Vladimirovic; Gusina, Anastasia Andreevna (History, Archeology and Ethnography of the Caucasus, 2025)
The paper presents the results of the perforation study of a female cranium fragment from burial 9, kurgan 1 of the Urukh II burial ground located near the village of Urukh, Leskensky area of the Kabardino-Balkarian Republic. The anthropological materials come from a burial that is attributed to the North Caucasian culture of the developed stage of the Middle Bronze Age. In the course of studying and describing the skull fragment defect, the Russian researchers` recommendations were used. The area of the trepanation was studied using a high-resolution video microscope ( x30 and x50) and a microfocus X-ray apparatus PRDU-02. As a result of the study, it was possible to establish that the defect on the female skull fragment from burial 9, kurgan 1 of the Urukh II burial ground is a trepanation case performed using the drilling method. The person survived the e procedure, as evidenced by the traces of denser skull bone-plates closure. The procedure might have been performed for therapeutic purposes. Analogies of this kind of manipulations were found in the Western Asian territory (Ikiztepe and Acemkhöyük) and date back to the Early and Middle Bronze Age. The trepanation performing skills using the drilling method in the North Caucasus population of in the Middle Bronze Age may be associated with the traditions common among the Mesolithic-Neolithic cultures in Anatolia and Ukraine.